Everyday Violence and Mental Health: A Study from the Family Perspective (Boletín Semillero de Investigación en Familia, 2026)
Introduction: Everyday violence within the family environment constitutes a public health problem that affects the coexistence and mental well-being of its members. Objective: To analyze forms of violence present in the daily lives of families in Villavicencio and their impact on mental health. Materials and methods: A qualitative study using the Grounded Theory methodology was conducted. Ten semi structured interviews were administered using theoretical sampling. The information was transcribed, coded, and analyzed using open, axial, and selective coding. Results: The emerging categories were: social determinants, forms of violence, perceptions of the impact on mental health, coping strategies, support networks, and role distribution. The study identified the economic, institutional, physical, psychological, verbal, and environmental forms of violence. Conclusions: Families report emotional effects such as anxiety, mood swings, emotional lability, and stress resulting from violence, and they use strategies such as dialogue, respect, mutual support, and legal mediation to reduce its impact.
Keywords: Mental health; Family; Violence; Social determinants; Family well-being; DeCS sources, 2025